PENGARUH KNOWLEDGE SHARING TERHADAP KINERJA KARYAWAN KANTOR PERWAKILAN BANK INDONESIA PROVINSI SULAWESI UTARA - Leonardo Memah; Riane Jhonly Pio; Sonny Gerson Kaparang (JURNAL ADMINISTRASI BISNIS, 2017)
This study purposed to analyze the influence of knowledge sharing towards employee performance at (Perwakilan Bank Indonesia office/Representative office of Bank Indonesia) in North Sulawesi province. Whereas the purpose of this study is to determine the influence of knowledge sharing towards employee performance. Knowledge sharing is measured by Donating Knowledge Indicator and knowledge collecting (de Vries et al, 2006). While the employee performance is measured by the quality of work, quantity of work and timeliness (Hasibuan 2006). The sample is employee of Bank Indonesia North Sulawesi as many as 47 people that taken from the 53 people of the total number of employee population. Data collection techniques in this study is the observations and questionnaires. Data analysis technique used in this study is simple linear regression. Data were processed using SPSS version 17.0. The results showed knowledge sharing has a positive and significant impact towards employee performance. Based on the obtained value of R Square is 0.387. which means that 38.7% of the employee performance (Y) can be explained by knowledge sharing (X). While the remaining 72.3% can be explained by other variables that was not researched in this study.Keywords: Knowledge Sharing, Employee Performance